Analisis Model Pembelajaran Bilingual yang Tepat Diterapkan Pada Siswa Sekolah Dasar - Nugroho, Gibran Fadil; Bahrudin, Zaini; Pradini, Uny Fita; Saputro, Gabril Aji; Permatasari, Sievera Fadilla; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper discusses the analysis of appropriate bilingual learning models applied to elementary school students. With the increasing need for English proficiency as a global communication tool, it is essential to implement effective teaching methods at the primary level. This study identifies several learning models, including Teams Games Tournament (TGT), Make A Match, ICCARE based on media, Inside Outside Circle, and Edu Fun, which can enhance students’ language and academic skills. Each model has its own advantages and challenges; however, overall, the application of these models is expected to improve students’ motivation and abilities in English. Through interactive and enjoyable approaches, students are anticipated to be more actively engaged in the learning process, thereby optimizing their vocabulary acquisition and communication skills. This research aims to provide insights for educators in designing more effective and engaging teaching strategies in the elementary school environment.